Journal Scan: Updates from Important Trials in Cardiology of 2022 (4th quarter of 2022) - Cader, F Aaysha; Khan, Saidur Rahman (Ibrahim Cardiac Medical Journal, 2023)
Abstract not available Ibrahim Card Med J 2022; 12 (2): 67-71